Differences between cardiorespiratory fitness in adult men with asymptomatic or mild SARS-COV-2 infections - Nia Sri Ramania; Tommy Apriantono; Bagus Winata; Rini Syafriani; Samsul Bahri; Maria Immaculata Iwo; Ashari Budi Nugraha (Physiotherapy Quarterly)
Introduction This study aimed to measure and compare CRF levels between COVID-19-infected adults with asymptomatic and mild symptoms.